Scientific Literacy Skills for Non-Science Librarians: Bootstrap Training - Christina A. Peterson; Sandra Kajiwara (Issues in Science and Technology Librarianship)
Adding scientific literacy to the skill set of permanent non-science and part-time adjunct librarians became a major focus of a staff development program at San Jose State University Library. The Library's one reference desk is busy, and librarians field questions from all disciplines. Changing staffing patterns in the Reference Department have necessitated the use of more adjuncts at the reference desk. A proliferation of web-based scientific information sources was overloading students and the librarians who serve them at Reference. In order to determine our most pressing training goals, we administered a survey to all reference personnel, discovering that librarians in the social sciences and humanities and adjunct librarians felt a knowledge deficit in chemistry, health sciences, and engineering, among other disciplines. The adjuncts, in particular, wanted to be brought up to speed in several aspects of science and technology librarianship, including the nature of science and its literature, typical undergraduate and graduate science students' information requirements, how to use both electronic and print sources in the sciences, and when to refer questions to science librarians. We put into place Bootstrap Training, a program for integrated groups of full-time and adjunct librarians. In this paper we describe an initial training-needs questionnaire distributed to all reference personnel, the implementation of a staff development program with scientific literacy goals, evaluation of the program, and implications for replicating the training in other library settings.